Grid-like residential layout: vulnerability to burglary / Saniah Ahmad Zaki - Ahmad Zaki, Saniah (Institute of Graduate Studies, UiTM, 2016)
Very few studies examined the relationship of the street patterns (or street layouts) and crime. Amongst those who looked at the relationship between street patterns and crime, movement of people in the street appeared to be related. Nevertheless, the explanation to how crime is affected by movement in the street appears contradictory. It has been suggested in a study that crime is higher in the more used streets (integrated spaces), whereas in another, it is higher in the less used streets (segregated spaces). Even within space syntax-based studies, which looked at the relationship between crime and spaces (different street types), concurs it is generally safer in the more used streets (integrated spaces). The syntax-based study, which used a robust technique of computer analysis that allows spaces to be analysed quantitatively, suggested that spaces interact together to influence crime so that burglars select the most vulnerable spaces within an area. It was deduced in that study, a safer layout would be one that have interconnected or integrated through streets, with dwellings facing out on to both sides of the streets. The main aim of this study was to examine the correlation of grid-like layouts on burglary rate and how different variations of grids affect the probability of burglary in that area. Six neighbourhoods in a local council area in the Klang Valley were selected based on common attributes….